Penguatan Literasi Digital Siswa dan Guru melalui Canva for Education di SDN Arjasa 1 Jember - Andriyani, Fitriya; Endro Sugiartono; Arisona Ahmad; Dessy Putri Andini; Sugeng Hartanto (Universitas Muhammadiyah Gresik, 2025)
The development of digital technology has a major impact on the world of education, especially in improving the quality of interactive and interesting learning media. One platform that can be utilized is Canva for Education, a web-based graphic design application designed to support creative teaching and learning processes. Despite its great potential, the use of Canva for Education at SDN Arjasa 1 Jember is still relatively minimal due to limited understanding and lack of training for teachers and students. The majority of the learning process at this school is still conventional, which has an impact on decreasing students' interest in learning. The form of activity to answer this challenge is in the form of socialization activities and training in the use of Canva for Education which aims to improve teachers' digital competence and encourage students' creativity in creating visual learning media. This activity was provided by lecturers at the Jember State Polytechnic. With this training, it is hoped that a more interesting learning atmosphere will be created, as well as encouraging the mastery of 21st century skills such as creativity, communication, collaboration, and problem solving for students from an early age.